Analysis Of Antenatal Care (ANC) Service Quality And Service Facilities On Patient Satisfaction Through Health Workers’ Competence As Mediating Variable - Sri Isna Amelia Ahmad; Retno Endah Supeni; Ni Nyoman Putu Martini (UNIVED Press, 2026)
This study aims to examine the influence of service quality and service facilities on patient satisfaction in antenatal care (ANC) services through the mediating role of health worker competence among third trimester pregnant women in community health centers (Puskesmas) across Jember Regency. Utilizing a quantitative approach with a cross-sectional design, data were collected from 255 respondents using Likert-scale questionnaires and analyzed through Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that both service quality and service facilities significantly affect patient satisfaction directly and indirectly through health worker competence. Competence emerged as the strongest predictor, highlighting its essential role in enhancing maternal satisfaction. The model demonstrated adequate predictive power with R² values of 0.637 for patient satisfaction and 0.482 for competence. These results underscore the importance of integrated improvements in service infrastructure and human resource capacity to optimize ANC delivery and maternal health outcomes, particularly in low- and middle-income country contexts.